Aid, Shocks, and Growth - Collier, Paul (World Bank, Washington, DC, 2014)
Analysis of the relationship between aid and growth by Burnside and Dollar found that the better a country's policies, the more effective aid is in raising growth in that country. But this result has been criticized for being sensitive to choice of sample and for neglecting shocks. The authors incorporate export price shocks into the analysis of aid's effect on growth. They construct export price indices using the approach pioneered by Deaton and Miller. They locate shocks by differencing the indices, removing predictable elements from the stationary process, and normalizing the residuals. Extreme negative shocks are the bottom 2.5 percent tail of this distribution. Introducing these extreme shocks into the Burnside-Dollar regression, the authors find that they are highly significant: unsurprisingly, extreme negative shocks reduce growth. Once these shocks are included, the Burnside-Dollar results become robust to choice of sample. Moreover, the adverse effects of negative shocks on growth can be mitigated through offsetting increases in aid. Indeed, targeting aid to countries experiencing negative shocks appears to be even more important for aid effectiveness than targeting aid to countries with good policies. But the authors show that, overall, donors have not used aid for this purpose.